The Effect of a Mixed-Starter Culture of Lactic Acid Bacteria on the Characteristics of Pickled Orange-Fleshed Sweet Potato (Ipomoea batatas L.) - NETI YULIANA; SITI NURDJANAH; MIKA MARGARETA (Indonesian Society for microbiology, 2013)
In this study, fermentation process was carried out on orange-fleshed sweet potato cubes to produce sweet potato pickle using a mixed culture of Lactobacillus plantarum and Leuconostoc mesenteroides at 30 °C over 12 days period. Spontaneous fermentation was also performed as a control. Samples were withdrawn at various time intervals for analyses of reducing sugar content, total number of lactic acid and non-lactic acid bacteria, lactic acid concentration, pH, and sensory attributes. The results showed that using a mixed culture of L. plantarum and L. mesenteroides could greatly reduce contamination of non-lactic acid bacteria, retaining low amount of reducing sugar, rapidly producing lactic acid and consequently decreasing pH value of the pickle, as well as giving better sensory score. After 12 d of fermentation, sample of pickle inoculated with mixed culture showed the following characters: total lactic acid content 0.5%, total lactic acid bacteria 8.46 log10 CFU mL-1, total non-lactic acid bacteria 1 log10 CFU mL-1, total reducing sugar 0.84 g L-1, texture 64.92 mm 50 g-1 s-1, and hedonic sensory score for both taste and aroma 4 (like) in a scale of 5. These results indicated the potential ability of the mixed culture of lactic acid bacteria to improve the quality of the pickle fermented spontaneously.